The Flux and Provenance of Dust Delivered to the SW Pacific During the Last Glacial Maximum. Issue 12 (1st December 2020) - Trudgill, M. D.; Shuttleworth, R.; Bostock, H. C.; Burke, A.; Cooper, M. J.; Greenop, R.; Foster, G. L.
Abstract: Atmospheric dust is a primary source of iron (Fe) to the open ocean, and its flux is particularly important in the high nutrient, low chlorophyll (HNLC) Southern Ocean where Fe currently limits productivity. Alleviation of this Fe limitation in the Subantarctic Zone of the Atlantic by increased dust‐borne Fe supply during glacial periods has been shown to increase primary productivity. However, previous work has found no such increase in productivity in the Pacific sector. In order to constrain the relative importance of Southern Ocean Fe fertilization on glacial‐interglacial carbon cycles, records of dust fluxes outside of the Atlantic sector of the Southern Ocean at the Last Glacial Maximum (LGM) are required. Here we use grain size and U‐series analyses to reconstruct lithogenic and CaCO3 fluxes and Nd, Sr, and Pb isotopes to ascertain the provenance of terrigenous material delivered to four deep water cores in the SW Pacific Ocean over the last 30 kyr. We find evidence for an increase in the relative proportion of fine‐grained (0.5–12 μm) terrigenous sediment and higher detrital fluxes during the LGM compared to the Holocene. The provenance of the LGM dust varied spatially, with an older, more "continental" signature (low εNd, high 87 Sr/ 86 Sr) sourced from Australia in the northern cores, and a younger, more volcanogenic source in the southern cores (high εNd, low 87 Sr/ 86 Sr), likely sourced locally from New Zealand. Given this increase in lithogenic flux to the HNLC subantarctic Pacific Southern Ocean during the LGM, factors besides Fe supply must have regulated the biological productivity here. Key Points: We present evidence for increased dust flux to the SW Pacific at the Last Glacial Maximum Australian dust fluxes increased to the north and New Zealand dust fluxes to the south during the Last Glacial Maximum There is little evidence for associated enhanced biological productivity